Comparison between Several Muscle Strength and Cardiorespiratory Fitness Indices with Body Composition and Energy Expenditure in Obese Postmenopausal Women - Bellefeuille, P.; Robillard, M.-E.; Ringuet, M.-E.; Aubertin-Leheudre, M.; Karelis, A. D. (International Journal of Sports Medicine, 2013)
The purpose of this study was to compare the relationship of several muscle strength and cardiorespiratory fitness indices with body composition and energy expenditure in obese postmenopausal women. This was a cross-sectional study involving 72 obese postmenopausal women (age: 60.0±4.8 years; body mass index: 34.1±3.5 kg/m2). Muscle strength was determined by hand dynamometer and cardiorespiratory fitness was measured by indirect calorimetry. Muscle strength and cardiorespiratory fitness were expressed in absolute (kg and L/min, respectively) and in relative values (kg/body weight (BW) and kg/lean body mass (LBM) for muscle strength and ml/min/kg BW and ml/min kg LBM for cardiorespiratory fitness). Body composition was measured using dual energy x-ray absorptiometry. Anthropometric (waist and thigh circumference), physical activity energy expenditure and daily number of steps (SenseWear armband) as well as blood pressure were also assessed. Correlations of muscle strength and cardiorespiratory fitness indices with body composition and energy expenditure showed several similarities, however, several variations were also observed. Furthermore, our results showed that age and waist circumference were the primary independent predictors for the muscle strength indices, explaining 22–37% of the variance and % body fat and age were the primary predictors for the cardiorespiratory fitness indices, explaining 18–40% of the variance. In conclusion, the present study indicates that the different methods of expressing muscle strength and cardiorespiratory fitness may display several variations and similarities with body composition and energy expenditure associations. Therefore, interpretations of relationships between muscle strength and cardiorespiratory indices with body composition and energy expenditure factors should take in account the method used to express them.
Keywords: hand dynamometer; peak oxygen consumption; dual energy x-ray absorptiometry; waist circumference; sensewear armband